Building Successful Partnerships A Production Theory of Global Multi-Stakeholder Collaboration - Buckup, Sebastian; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Multi-stakeholder partnering has become the 'new mantra' of decision-makers in business, government and civil society. Yet our understanding of what drives success and failure in these institutions remains incomplete. The book introduces a production theory which describes how the relationship between contributions and outputs influences behaviour, and suggests how technology, leadership and governance should be aligned to make partnerships work.
Keywords: Economics; Economics/Management Science; Economics general